Pengembangan E-Modul Fisika Berbasis Model Problem Based Learning Materi Getaran Harmonis Sederhana - Feziyasti, Azifa; Putra, Amali; Hidayati, Hidayati; Sundari, Putri Dwi (Pendidikan Fisika UIN Alauddin Makassar, 2024)
This research was conducted to analyze the need for developing e-modules based on the Problem Based Learning model. The research was conducted use literature study and field observation. The type of research conducted is descriptive qualitative research. In this field study, data collection was obtained by analyzing the needs of teacher from interview sheets and analyzing the needs to students from questionnaire instruments. Systematically developed e-module features images, animations, videos, and interactive quizzes that available for students to use independently. E-modules developed based on the Problem Based Learning model with features in the Flip PDF Proffesional application. Teacher needs analysis in the form of interviews was conducted for obtain information in the form of whether teachers use e-module, the types of teaching materials used, and the learning models used in class. As for the needs analysis on 36 students of class X IPA 2, it is known that students are allowed to use cellphones in class, besides that the school also provides wi-fi for learning needs. As many as 94.4% of students are happy if the teaching materials have features of images, animations, videos and interactive quizzes, 66.7% of students feel that the teaching materials used are not sufficient for their learning needs and students feel that the material on simple harmonic vibrations in the teaching materials is difficult to understand. In addition, 88.9% of students needs study resources to understood independently and 91.7% of students are interested in learning using e-modules. From the results of the analysis, may be concluded that the importance of developing an e-module based on the Problem Based Learning model of Simple Harmonic Vibration material.